A marketing plan for McCafe Philippines - Olarte, Shaun Audrey Leandre (Animo Repository, 2004)
Keeping ahead involves continuous hard work to enhance the reputation of the brand, coupled with product innovation based on detailed market research that indicates how to please customers. This paper examines the positive way in which McDonalds is responding to changing customer habits and increased levels of competition. Today, many people live busy lives and place great importance and convenience when buying and paying for goods and services. They are attracted by modern, quick service products such as drive-in car washes, mobile phones and ready meals. For many people (though not all), this emphasis on instant service is a winning formula, particularly for younger people and young families. However, modern consumers of all ages are seeking experiences that are more individualized than in the past. All organizations need to be in touch with their business environment in order to make sure that what they do fits with customer expectations. McDonald's is looking to provide appropriate solutions to these changing trends. Even mature markets can have gaps in provision that leave some potential to these changing trends. Even mature markets can have gaps in provision that leave some potential customers unsatisfied. The McCafe development is the result of intensive market research that has identified a group of potential customers that had remained largely untapped. McDonald's recognizes the importance of listening to the needs and requirements of this substantial group of users. McCafe provides an avenue for McDonald's to target these consumers by offering high quality coffee served by specially trained café staff in a café style environment. McDonald's has defined its target market clearly. The McCafe target market is customers who appreciate quality coffee and who want an excellent product in an attractive, undaunting environment. This concept has already worked well in Australia and New Zealand where the café concept is less developed than in the US. These examples suggest that while McCafe works well and is profitable in urban locations in the Philippines and become increasingly flooded with new entrants to the café market, competition will continue to increase as will the need to continue to look for new ways to compete within cities. McCafe offer a new group of customers a way of taking time out with a good cup of coffee. McCafe positions itself in the AB and C classes, which accounts for 7% in the coffee drinking population of Metro Manila. Demographically this group is primarily yuppies and business alike and ranges from 25-34 years old. Many within this group have young families. McCafe are designed to offer them a place to meet friends and enjoy a quality coffee experience as well as keep the children fed and entertained. The service plan includes programs and strategies that will increase sales through consumption of beverage and food since McCafe plans to make better food presentations and aggressive advertising campaign. In addition, the proposals are intended to increase the level of patronage of those who are already aware of the establishment, and at the same time, attract others belonging in the same market. The Marketing Service Plan includes detailed costing of all service development programs, pricing programs, sales and distribution and promotional programs Evaluation and monitoring of the plan will be done through a comparative study of the market and monitoring of financial statements, and from customer feedbacks.